EDITORIAL PAPER - ENGINEERING - JT ADMIN (Journal of Techniques)
The Journal of Techniques is an open access journal interdisciplinary peer-reviewed journal that calls for research work in different technical fields of imposing sciences. The journal deals with the state-of-the-art research in engineering, and requests both theoretical and/or practical works that can tackle the limitations and challenges of the latest developments in different fields of engineering techniques. Therefore, the journal aims to publish original and high-quality research papers in techniques of the engineering fields. The articles must be original writing that improves the current form of knowledge in the specified subject area. Applied articles are adequate if they are valuable to the engineering society on how to present technology or methodology that is novel. Survey, research reports, express communications, and review articles are acceptable if they present useful efforts. The journal seeks experimental and practical work that can overcome the limitations and drawbacks of gaps in the latest research in different fields of engineering. Moreover, the journal will publish work regarding simulation results and practical case studies. The topics considered include, but are not restricted to, electrical and electronic engineering, communications engineering, computer engineering, control and automation engineering, laser and optics engineering, medical engineering, biomedical engineering, mechatronics, mechanical engineering, material engineering, nanotechnology, thermal engineering, energy and renewable energy, chemical engineering , petroleum engineering, civil and structural engineering, surveying and geomatics engineering, water-resources engineering, environmental engineering, safety, risk management and quality, architecture, and technical education.